Narratives of Young Men With Injecting Drug Use Histories Leaving Adult Prison. (September 2018) - Walker, Shelley; Higgs, Peter; Stoové, Mark; Wilson, Mandy
This research focuses on an under-examined aspect of the post-release prison trajectory for a seldom-researched cohort. Narratives of the immediate days/weeks surrounding release were gathered from young men with histories of injecting drug use (IDU). Twenty-eight participants (aged 19-24) released from adult prisons in Victoria, Australia, participated in face-to-face in-depth qualitative interviews after release. Analysis of findings through the lens of a "risk environment" framework reveals how their experiences were compromised by risk factors embedded in the physical spaces and social situations they inhabited, as well as the multi-sectoral policy environments under which they were governed. A complex interplay between these factors, young men's drug use and broader issues of structural vulnerability, including institutionalization and social disadvantage, combined to limit young men's chances of "success" 1 on the outside. Narratives provide evidence for interventions that transform risk environments into enabling environments, thereby promoting a more successful transition from prison to community for young men with IDU histories.